Shifting Landscapes: Influence of Climate Change on India’s Rural Economies and Livelihoods - Kumar S, Harish; Priyadharsini, S; Arjunan, R; Lovelina Little Flower, FX (South Asian Journal of Social Sciences and Humanities, 2025)
This article is intended to analyse the effects of climate change on the rural economy. Climate change and variability affect everyone and every part of the world. It is a serious threat to individual livelihoods and ways of making a living. The study conducted a rapid literature review to provide a timely synthesis of the existing evidence. Changes in climate conditions have significantly impacted ecosystem degradation in recent decades, with dire effects for the rural population, which mostly depends on agriculture and fishing for a living. Undoubtedly, a changing climate has a direct and indirect impact on the economy. Countries like India, whose GDP largely depends on the rural economy, have faced enormous challenges in the last two decades. Many researchers have tried to find the changes in the rural economy and its crisis from an economic and political point of view, rather than Climate change and its impact, which seems to be a simplistic view. However, this article attempts to critically examine the changing rural economies in the context of climate change. This study offers a fresh perspective by analysing rural economic crises through the lens of climate change rather than purely economic or political factors, thereby revealing how environmental shifts fundamentally reshape livelihoods in India.